A mobile phone-based analyzer for quantitative determination of urinary albumin using self-calibration approach - Mathaweesansurn, Arjnarong; Maneerat, Noppadol; Choengchan, Nathawut (My University, 2017)
This work demonstrates use of a smart mobile phone installed with an Android application, termed ‘Albumin smart test’, as an analyzer for quantitative determination of urinary albumin. The reaction between albumin and tetrabromophenolphthalein ethyl ester (TBPE) in the presence of Triton X-100 was employed for detection principle.The mobile phone was exploited with the sample cassette and the test paper. One sample cassette composes of two holders for accommodation of control and test samples. The test paper was designed in order to contain standard colorimetric strip and space for situating the sample cassette. Optical images of the strip and the samples were simultaneously captured in a single shot by a digital camera of the mobile phone and were digitally processed by the developed application for quantification of the albumin concentration based on self-calibration approach. With the advantage of self-calibration, the albumin test by our mobile phone can be performed in ambient light without using any extra module integrated with lighting control device. The other advantages are portability, ease of implementation and rapid analysis (3 min) with high precision (RSD ≤ 2.5%) and high accuracy (Recovery = 98.7% ± 1.6). The mobile device was successfully applied to diagnosis of microalbuminuria.
Keywords: Albumin; Image processing; Mobile phone; Quantitative determination; Self-calibration; Urine